Evaluation of the Developed and Produced Computer Generated Instructional Materials (CGIM) for College Geometry - Bacio, Jr., Salvador P.; Sagge, Jr, Roberto G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The tripartite function of faculty members in higher education includes instruction, research, and extension. Built-in into this function was to produce of instructional materials for students’ and teachers’ consumption. The objective of this study was to evaluate computer-generated instructional materials (CGIMs) used in college geometry courses. To attain this, the researchers used descriptive-evaluative design. The respondents were the twenty (20) teachers teaching Geometry and Curriculum Development. The instruments used were the worktext and multimedia efficiency rating scale, usefulness, accuracy, completeness, and appropriateness rating scale. The result shows that in terms of physical attributes, objectives, content, exercises, and evaluation, the worktext has a “very high” efficiency level while in terms of content, physical attributes, and visual clarity the multimedia presentation achieved a “very high” efficiency level. It was also found that in terms of usefulness, accuracy, completeness, and appropriateness, the developed CGIM has attained a “very high” level. This means that the developed CGIM achieved an excellent level of instructional material development. CGIM is recommended as a way to improve the achievement, mental habits, and problem-solving skills of Geometry students.